2017
DOI: 10.1016/j.memsci.2016.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Pebax®1657/Graphene oxide composite membranes for improved water vapor separation

Abstract: In this study composite mixed matrix membranes containing hydrophilic microphaseseparated block copolymer (Pebax ® 1657) and graphene oxide nanosheets were prepared using a dip coating method. Water vapor and N 2 gas permeation were measured as a function of different parameters: (i) layer thickness, (ii) content of graphene oxide (GO), and (iii) content of reduced GO. Surprisingly, a concentration of only 2 wt% of GO nanosheets well dispersed in the Pebax layer boosted the selectivity 8 times by decreasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Even after addition of CPD, morphology of membrane does not change to too much extent (Figure ). CPD is entrapped through hydrogen bonding between OH group in CPD and polar NH, CO groups present in PEBA (as explained in FTIR and DSC) . There is no significant defect or crack in the prepared membranes.…”
Section: Resultsmentioning
confidence: 89%
“…Even after addition of CPD, morphology of membrane does not change to too much extent (Figure ). CPD is entrapped through hydrogen bonding between OH group in CPD and polar NH, CO groups present in PEBA (as explained in FTIR and DSC) . There is no significant defect or crack in the prepared membranes.…”
Section: Resultsmentioning
confidence: 89%
“…Although the Pebax ® 1657 Raman spectrum shows weak signals owing to its fluorescence, three peaks can be distinguished at 1133, 1305 and 1454 cm -1 related to the C-O and C=O vibration modes. 38 Signals in the 1300-1800 cm -1 range can be seen in the P84 ® spectrum. The signals at 1376 and 1435 cm -1 correspond to the C=O in-phase stretching mode.…”
Section: Membrane Characterizationmentioning
confidence: 96%
“…8 Assuming the perfluorinated polymer layers in the composite membranes have the same CO 2 and CH 4 permeabilities as pure membranes of the polymers (Table 3), then the respective average permeabilities of the 6FDA-TMPDA and PIM-1 layers can be determined through Equation (3), and are provided in Table 6. This assumption is valid because of the poor solvation properties of the Teflon AF1600 polymer, meaning it does not integrate, blend or be modified by the underlying 6FDA-TMPDA or PIM-1 layer structure.…”
Section: Single Gas Permeabilitymentioning
confidence: 99%
“…Previous research has demonstrated that exposure to water vapor can reduce the permselectivity of the polyimide 6FDA-TMPDA by 50% [6] and for high performance PIM-1 membranes by 38% [7]. The majority of the research has focused on water removal from the feed stream, in dehydration applications [8][9][10][11][12][13][14]. In contrast, perfluorinated polymers Teflon AF1600 and Hyflon AD60 membranes demonstrate significant resistance to separation performance loss in the presence of water vapor [15].…”
Section: Introductionmentioning
confidence: 99%